High dose rate brachytherapy three-dimensional gel dosimetry using optical computed tomography readout. (August 2019) - DeVries, DA; Joshi, C; Schreiner, LJ
Abstract: The cause and removal of streaking artifacts from catheters within radiochromic 3D dosimeters was investigated to allow the use of these dosimeters for high dose rate (HDR) brachytherapy applications. The OSC-TV iterative reconstruction algorithm's ability to remove the streaking artifacts from one or more catheters was validated using external beam irradiations and leuco crystal violet (LCV) micelle gels. One and two catheter HDR plans were then delivered to LCV gels. Dose volumes from the gels were reconstructed with the OSC-TV algorithm, calibrated, and registered to treatment planning system dose volumes, and were shown to be artifact free and in agreement with the expected values.